Targeting Metastatic Cancer: Disseminated Tumor Cells and Premetastatic Niches - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Metastases are simply known as cancers spread to another part of the body, and often be responsible for the severity of cancer prognosis. Somehow, the complex mechanisms of metastases are not fully understood yet.CONTENT: The characteristic of cancer is akin to a never-healing wound. Cancer cells are plastic and dynamic as they build their niches and developed into metastases, even when they seem dormant. Therefore, cancer cells can survive the immune system. Recent research has shown the distinct biology of metastasis-initiating cell, which leads to tumor development in distant organs, immune surveillance evasion, and co-option of metastatic micro-environments. Effective cancer therapies must consider the regenerative states of metastatic malignancies and have careful observation of patient phenotypes.SUMMARY: This review aimed to provide an insight on genesis and characteristics of metastases, starting from its seeding and dormancy, until the advance phase. Thus, developing therapy for cancer metastases should not start as it grows, but even as earlier strategies since the primary tumor was detected.KEYWORDS: cancer metastasis, DTC, CTC, CSC, dormancy, pre-metastatic niche, plasticity